2017
DOI: 10.1002/pros.23458
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term oral exposure to safe dose of bisphenol A in association with high‐fat diet stimulate the prostatic lesions in a rodent model for prostate cancer

Abstract: The results indicated that the methodology used was effective in generating metabolic changes, which directly compromised prostatic homeostasis. Diet and BPA appear to modulate the activation of the AR pathway and thereby optimize tumor establishment in the gerbil prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…14 These findings are consistent with mounting evidence that prenatal and neonatal exposure in rodents to BSA, even at the current safe dose level (<50 μg/kg/d) accepted by the US Food and Drug Administration and the US Environmental Protection Agency and the European Food Safety Authority, 5 is linked to changes in sexual differentiation, defects in male and female reproductive tracts, meiotic abnormalities in fetal oocytes, complications during pregnancy, and increases in malignancies in adult animals. 15 -17 Adolescence is a key point for gonadal development, endocrine hormone synthesis, and metabolic regulation. Therefore, we selected pubertal male mice as the research model to study the effects on their fertility to exposure at “safe” dose and higher dose of BPA.…”
Section: Discussionmentioning
confidence: 99%
“…14 These findings are consistent with mounting evidence that prenatal and neonatal exposure in rodents to BSA, even at the current safe dose level (<50 μg/kg/d) accepted by the US Food and Drug Administration and the US Environmental Protection Agency and the European Food Safety Authority, 5 is linked to changes in sexual differentiation, defects in male and female reproductive tracts, meiotic abnormalities in fetal oocytes, complications during pregnancy, and increases in malignancies in adult animals. 15 -17 Adolescence is a key point for gonadal development, endocrine hormone synthesis, and metabolic regulation. Therefore, we selected pubertal male mice as the research model to study the effects on their fertility to exposure at “safe” dose and higher dose of BPA.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several risk factors, including age, genetic factors, androgen dependence, sex hormones, environmental factors, and diet, have been implicated in PCa pathogenesis. 9,10 The activation of oncogenes and the suppression of tumor-suppressing genes also perform major contributions to PCa oncogenesis. 11,12 However, the mechanisms involved in the development and progression of PCa are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…A histopathological study confirmed that long-term BPA exposure and a high-fat diet induced lesions typical of proliferative and inflammatory processes; additionally, some metabolic changes altered the normal prostatic function (107). The dorsolateral lobe was the most affected, showing a high number of lesions in rats administered with BPA and a diet rich in fatty acids, suggesting an additive effect (107). In general, BPA increased the number of epithelial alterations and inflammatory foci, and adding a hypercaloric diet affected similar signaling pathways (107).…”
Section: Effects Of Edcs On Prostatementioning
confidence: 65%
“…BPA exposure has been associated with obesity and endocrine/metabolic disease (106). A histopathological study confirmed that long-term BPA exposure and a high-fat diet induced lesions typical of proliferative and inflammatory processes; additionally, some metabolic changes altered the normal prostatic function (107). The dorsolateral lobe was the most affected, showing a high number of lesions in rats administered with BPA and a diet rich in fatty acids, suggesting an additive effect (107).…”
Section: Effects Of Edcs On Prostatementioning
confidence: 88%